The Effect of Profitability and Capital Structure on Company Value - Siahaan, Trioksa; Fu Putra, Arveren (Economics and Business Journal (ECBIS), 2024)
This study examines the effect of profitability and capital structure on firm value. Profitability, measured by Return on Assets (ROA) and Return on Equity (ROE), reflects the company's ability to generate profits from its operations. Capital structure, represented by the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR), indicates the proportion of debt and equity used to finance the company. The research sample consists of companies listed on the Indonesia Stock Exchange (IDX), selected through purposive sampling based on specific criteria. Data analysis was conducted using multiple linear regression models. The results show that profitability and capital structure both have a positive and significant effect on firm value. Profitability contributes to increasing firm value by attracting investors and enhancing market confidence. Meanwhile, an optimal capital structure, particularly the prudent use of debt, can also increase firm value by lowering the cost of capital. The study suggests that management should focus on improving profitability and maintaining an optimal capital structure to maximize firm value